Over expression of Her- 2 neu in ovarian surface epithelial carcinoma in a sample of Iraqi patient at Al-kindy Teaching Hospital. - AL-Kurtas, Mohammed , Abdul Mahdi (AL-Kindy College Medical Journal, 2013)
Background: Although expression of the HER-2/neuoncogene may be of some prognostic importancein advanced ovarian cancer, its role in early-stagedisease has not been established. The current studyexamined the prevalence and significance of HER-2/neu expression in different grades of different typesof surface epithelial ovarian carcinoma.Methods: Thirty eight female patients with surfaceepithelial ovarian cancer were included in this study.The blocks of corresponding formalin fixed, paraffinembeddedovarian biopsies were retrieved from thearchives and hematoxylin-eosin slides of each ovarianbiopsy were reviewed and marked their grades ofdifferentiation , then a new sections from each samplestained by her2/neu as immunohistochemicaltechnique and classified according to degree ofintensity regarding to dependable scoring system ,also ten cases taken as control group from normalovarian tissue.Results :-Thirty eight sample of surface ovariancarcinoma were collected , twenty six were serousovarian carcinoma , eleven cases were mucinouscarcinoma type and one case was endometriodcarcinoma . The samples were classified according totheir histological types and according to their grading .The mean age of SC type was 54.52 with SD 7.17while the mean age of mucinous carcinoma was 49.36with SD 4.9. There is no significant relation betweeneach type and grading system ( P Value = 0.9 ) ,alsothere is no significant relation between age groupdistribution and types of ovarian carcinoma ( P value= 0.14 ).Instate that statically no significant relationbetween intensity of expression Her2/neu and highgrading of each types of collected sample ( P value=0.22) and this may be due to small sample size butstill there are obvious criteria showing that her2/neuexpression relatively increase in higher grade of eachtypes of studied ovarian surface epithelial carcinoma.Conclusion :-In conclusion, the overexpression ofthe HER-2/neu gene product appears to be an unusualoccurrence in early epithelial ovarian cancer and mayoccur less frequently than in advanced disease. Earlyovarian cancer will eventually progress to advanceddisease if undiagnosed and untreated, then, HER-2/neu overexpression does not appear to be a generalearly event in the development of ovarian cancer.Instead, it seems that increased expression develops inmany instances after the malignant phenotype hasalready arisen.